Products of Composition and Differentiation Operators from Bloch into QK Spaces - Shunlai Wang; Taizhong Zhang (Journal of Function Spaces)
The boundedness and compactness of the product of differentiation and composition operators from Bloch spaces into QK spaces are discussed in this paper.